The effect of competitive intelligence on competitive strategy and performance: study on cafes and restaurants in Malang, Indonesia - Asminah Rachmi; Diana Eka Poernamawati (Diponegoro International Journal of Business, 2020)
This study aims to investigate the effect of competitive intelligence to competitive strategy and performance of cafes and restaurant in Malang, Indonesia. Data analysis applying path analysis on 100 samples showed that competitive intelligence directly affects performance and indirectly through competitive strategy performance. These findings are expected to provide recommendations for strategic planning development efforts in the future for cafes and restaurants in Malang, and also to help in developing the best practices in responding the market change.